The understanding of concept of share waqf and the awareness of share waqf among the communities in UiTM Puncak Alam / Maryam Humaira Mohammad Adib - Mohammad Adib, Maryam Humaira (2019)
Waqf is one of the institutions that are important in Islamic Financial Institutions and it had been growing rapidly in Malaysia. Majority of people in Malaysia are Muslim but the lack of knowledge and awareness regarding waqf is the reason why our waqf institutions are not widely known. Share Waqf is a new scheme that has been introduced by the State Religious Islamic Council and it is easy for Muslim to do waqf because they do not need to spend a lot in share waqf. Since this scheme is a new scheme, not all Muslim in Malaysia are aware of this share waqf. Hence, the objectives of this study are to analyse the understanding of the concept of share waqf and the awareness about share waqf among the communities in UiTM Puncak Alam. There are 63 respondents who have been selected in order to complete this study. This study also analyses the data by using the Statistical Package for Social Science (IBM SPSS 21). Based on the finding, it can be concluded that the understanding of the concept of share waqf is at a moderate level while the awareness about share waqf is quite impressive. It can also be concluded that some of the respondents are lacking in knowledge but they seem interested with share waqf and they are willing to do it if given the chance.